Does motor imagery enhance stretching and flexibility? - Guillot, A.; Tolleron, C.; Collet, C. (Journal of Sports Sciences, 2010)
Although several studies have demonstrated that motor imagery can enhance learning processes and improve motor performance, little is known about its effect on stretching and flexibility. The increased active and passive range of motion reported in preliminary research has not been shown to be elicited by motor imagery training alone. We thus compared flexibility scores in 21 synchronized swimmers before and after a 5-week mental practice programme that included five stretching exercises in active and passive conditions. The imagery training programme resulted in selective increased flexibility, independently of the stretching method. Overall, the improvement in flexibility was greater in the imagery group than in the control group for the front split (F1,18 = 4.9, P = 0.04), the hamstrings (F1,18 = 5.2, P = 0.035), and the ankle stretching exercises (F1,18 = 5.6, P = 0.03). There was no difference in shoulders and side-split flexibility (F1,18 = 0.1, P = 0.73 and F1,18 = 3.3, P = 0.08 respectively). Finally, there was no correlation between individual imagery ability and improvement in flexibility. Psychological and physiological effects of motor imagery could explain the increase in range of motion, suggesting that imagery enhances joint flexibility during both active and passive stretching.